Labour Supply in New Zealand and the 2010 Tax and Transfer Changes - John Creedy; Penny Mok (New Zealand Government, The Treasury, 2015)
This paper examines the simulated labour supply responses to the personal tax and transfer policy changes introduced in New Zealand in 2010, and the implications for revenue and income distribution. The main changes examined are the increase in the GST rate from 12.5 to 15 per cent, along with reductions in personal income tax rates and increases in the main benefit payments and assistance to families with children, to compensate for the rise in GST. The simulated labour supply responses were obtained using the Treasury's behavioural microsimulation model, TaxWell-B. The 2009/10 Household Economic Survey (HES) was used. The combined effect of all policy changes is to increase average labour supply slightly for all demographic groups. Labour force participation of sole parents is simulated to increase by 0.86 percentage points. In considering separate components, the change in income tax rates is found to have the largest effect on labour supply. This is not surprising given that it affected a large proportion of the population while the changes to the benefit system and assistance to families with children apply only to certain groups. The reforms are found to be approximately distribution neutral, in terms of the Gini inequality measure of after-tax income per adult equivalent person.
Keywords: C25; J22; 330; Einkommensteuer; Steuerreform; Sozialpolitik; Umverteilung; Steuereinnahmen; Verteilungswirkung; Einkommensverteilung; Neuseeland